The Impact Of The "Marketing Mix 4P" Marketing Strategy On Purchasing Decisions For MSME Products In Sorong City - Ridwan, Akmal; Wijiastuti, Retno Dewi; Kamaluddin, Kamaluddin; Sanjaya, Erfandi Mukti (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
This study aims to analyze the understanding and implementation of the Marketing Mix 4P strategy by MSME actors and to examine its relationship with consumer purchase decisions as well as its impact on the welfare of both indigenous (OAP) and non-indigenous MSMEs in Sorong City. Using a mixed methods approach with a concurrent transformative design, data were collected through observation, in-depth interviews, questionnaires, and literature studies, employing multistage random sampling with 100 quantitative respondents and qualitative informants consisting of academics, MSME owners, marketing practitioners, government officials, and retailers. Data were analyzed using a convergent parallel mixed method, with SPSS 27 applied for regression, t-test, and F-test, and qualitative analysis conducted through Miles & Hubermans model using NVivo 14. The results reveal that, partially, product and place strategies have no significant effect on purchase decisions, while price and promotion strategies significantly influence consumer decisions, with promotion emerging as the most dominant factor. Simultaneous testing indicates that the four variables of the 4P marketing mix collectively exert a positive and significant influence on purchase decisions, contributing 65.7%. Qualitative findings further emphasize that consumers prioritize affordable pricing and attractive promotions over product quality and distribution location. These findings demonstrate that the application of the 4P marketing mix not only enhances purchase decisions but also positively impacts competitiveness, consumer loyalty, market expansion, and the welfare of MSME actors, both OAP and non-OAP, although challenges remain in improving product quality and distribution.